IMPLEMENTATION OF RESOURCE BASED LEARNING (RBL) MODEL THROUGH SCIENTIFIC APPROACH IN IMPROVING NATURAL SCIENCE LEARNING FOR THE FOURTH GRADE STUDENTS OF SDN 1 KLAPASAWIT IN ACADEMIC YEAR 2014/2015 - Khaeriyah, Elin (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: Implementation of Resource Based Learning (RBL) Model through Scientific Approach in Improving Natural Science Learning for the Fourth Grade Students of SDN 1 Klapasawit in Academic Year 2014/2015. The objectives of this research are to describe the steps in the implementation of resource based learning model through scientific approach and to improve learning process and learning outcomes of natural science learning with the topic of my living place about natural resources. This research is a collaborative Classroom Action Reseach (CAR). This research was conducted in three cycles. Techniques of collecting the data were observations sheets, interview, check list, test, and documentation. The conclusion of this research is the implementation of resource based learning model through scientific approach carried out with the appropriate steps can improve natural science learning with the topic of my living place for the fourth grade students of SDN 1 Klapasawit in the academic year 2014/2015. Keywords: resource based learning, scientific approach, natural science